Determinant Factors E-Satisfaction and Repurchase Intention of Investment Platform Users In Indonesia - Henny Dwijayani; Wahyudi Sofyan; Arief Yanto Rukmana; Etika Purnamasari; Jasman (SEULANGA SYSTEM PUBLISHER, 2023)
Together With The Level Of Financial Literacy Of The Indonesian Population, Which Has Increased Significantly, And Financial Digital Technology, Which Has Shown Positive Developments, The Development Of Retail Investors In The Capital Market In Indonesia Is A Very Good And Potential Moment For The Investment And Financial Industry In Indonesia. Regarding The Percentage Of Investors In The Capital Market, Indonesia Still Has Issues And Lags Behind Other Nations. The Economy Of A Nation Benefits From Having More Investors In The Capital Market. This Study Intends To Examine How E-Service Quality, E-Trust, E-Satisfaction, And E-Repurchase Intention Relate To One Another. The Route Analysis Approach Was Utilized To Analyse The Data And Provide The Research Findings For This 150-Respondent Study. The Findings Demonstrated That E-Service Quality Has A Direct Impact On Users' E-Satisfaction With Investment Platforms, E-Service Quality Has A Direct Impact On Users' Intention To Repurchase On One Investment Platform, And E-Service Quality And E-Satisfaction Have No Indirect Influence On Users' Intention To Repurchase Through Their E-Satisfaction.